ANALISIS KEBIJAKAN PAUD NASIONAL - Isma Patonah; Rima Sahaya; Cucu Atikah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is a research based on literature review (Library Reasearch). The purpose of this study is to analyze the National ECCE Policy as a coaching effort shown to children from birth to the age of six years and make ECCE policy as an educational guideline in implementing flexible learning programs in the context of fostering and developing children's potential. Currently, there are various forms of government policies given to Early Childhood Education (PAUD) nationally, which have been issued by the government which aims to develop quality Early Childhood Education (PAUD) through various policies such as the legislative system to technical matters of operational nature.